Peningkatan Hasil Belajar dalam Pembelajaran Matematika Materi FPB & KPK melalui Media Pembelajaran Papan Musi pada Siswa Kelas IV di SDN Damarsih Sidoarjo - Sarah Ramdhania; Shofiyun Nisa'; Nurul Istiqfaroh; Siti Syaria (Department of Education Faculty of Teacher and Training Education University of Jember, 2022)
The study aims to develop a learning medium called the musi (multifunction) board. The learning media we choose this time is particularly suitable for implementation in both the low classes and the high classes in elementary school or elementary school. This type of research is class action research (PTK). The English term is the classroom action research (car), a research activity carried out in class. Class action research (PTK) is a study activity that involves a class action that is carried out to solve the learning problems faced by teachers, improve and produce learning and try new things in learning for the improvement and the data-collection study that is used is interviews, tests and observations. Validation obtained by 97.5% which means the musi board learning media can be applied. Based on data already obtained, it could be concluded that knowledge or cognition of the ivs-ds class damarsi increased with the application of the musi (multi-function) learning media so that the action carried out in the study was said to be successful without further action.